Association of TRPM Channel Gene Polymorphisms with Systemic Sclerosis - Oztuzcu, Serdar; Onat, Ahmet M.; Pehlivan, Yavuz; Alibaz-Oner, Fatma; Donmez, Salim; Cetin, Gozde Y.; Demiryurek, Abdullah T. (Int Inst Anticancer Research, 2015)
Background/Aim: Systemic sclerosis (SSc) is an inflammatory disease characterized by vascular abnormalities and fibrosis. The aim of the present study was to investigate the possible role of transient receptor potential melastatin (TRPM) channel genes in the susceptibility and phenotype expression of SSc. Materials and Methods: A total of 339 patients with SSc and 302 healthy controls were studied. Genomic DNA was extracted from leukocytes of the peripheral blood, and 25 single nucleotide polymorphisms in the TRPM channel genes were analyzed by the BioMark HD dynamic array system. Results: There were marked increases in the CC genotype (94.7% vs 81.8%, p<0.0001) and C allele frequencies (97.0% vs. 90.1%, p<0.0001) in the TRPM3 rs1328142, and TT genotype (19.0% vs. 7.8%, p=0.0002) in TRPM5 rs34551253 (Ala456Thr) polymorphism in SSc patients when compared to controls. TRPM3 gene rs1328142 polymorphism was also markedly associated with disease phenotype. However, no associations with the other 23 polymorphisms studied were found. Conclusion: This is the first study to examine the involvement of TRPM channel gene variations on the risk of SSc incidence. Our results suggest roles of TRPM3 and TRPM5 gene variants in the susceptibility to or clinical expression of SSc in the Turkish population.
Keywords: Cation channels; haplotype; polymorphism; scleroderma; systemic sclerosis; transient receptor potential melastatin